PENGARUH KONSENTRASI PEMBERIAN PUPUK ORGANIK CAIR KIPAHIT TERHADAP PERTUMBUHAN DAN HASIL TANAMAN BAWANG MERAH SECARA HIDROPONIK - I MADE SUKERTA; I DEWA NYOMAN RAKA; IFTI NUR HIDAYAH (Universitas Mahasaraswati K. Mataram, 2023)
Shallots are commonly used for seasoning dishes, and have a function as a flavoring seasoning. Hydroponic cultivation of shallots axis system still depends on the use of AB Mix nutrients, and has a high price, besides AB Mix nutrition is an an-organic fertilizer. Liquid organic fertilizer kipahit as an alternative to hydroponic nutrition. The purpose of this study 1)knowing the effect of applying liquid organic fertilizer kipahit on the growth and yield of onion plants. 2) Knowing the percentage concentration of applying liquid organic fertilizer kipahit is effective against the growth and yield of onion plants. The research was conducted at BPTP Bali Agroinnovation Park located on Jalan By Pass Ngurah Rai, Pesanggaran, South Denpasar, Bali. The research was conducted from August 2022 to November 2022. The research method used was P1: 30% AB Mix, P2: 30% AB Mix + 20% POC Kipahit, P3: 30% AB Mix + 40% POC Kipahit, P4: 30% AB Mix + 60% POC Kipahit, P5: 30% AB Mix + 80% POC Kipahit, P6: 30% AB Mix + 100% POC Kipahit. The best percentage was given to the P6 treatment (100% kipahit liquid organic fertilizer) which had the highest results for each observation variable. The plant growth data obtained is then analyzed using analysis ANOVA and BNT. The concentration of kipahit liquid organic fertilizer that is suitable for use on onion plants hydroponically is 100 mL/liter because it has the highest fresh weight of tubers, which is 1.60 grams which indicates maximum plant growth